Measuring and comparing structural fluctuation patterns in large protein datasets - Fuglebakk, Edvin (2012)
Motivation: The function of a protein depends not only on its structure but also on its dynamics. This is at the basis of a large body of ex- perimental and theoretical work on protein dynamics. Further insight into the dynamics?function relationship can be gained by studying the evolutionary divergence of protein motions. To investigate this, we need appropriate comparative dynamics methods. The most used dynamical similarity score is the correlation between the root mean square fluctuations (RMSF) of aligned residues. Despite its usefulness, RMSF is in general less evolutionarily conserved than the native struc- ture. A fundamental issue is whether RMSF is not as conserved as structure because dynamics is less conserved or because RMSF is not the best property to use to study its conservation. Results: We performed a systematic assessment of several scores that quantify the (dis)similarity between protein fluctuation patterns. We show that the best scores perform as well as or better than struc- tural dissimilarity, as assessed by their consistency with the SCOP classification. We conclude that to uncover the full extent of the evo- lutionary conservation of protein fluctuation patterns, it is important to measure the directions of fluctuations and their correlations between sites.